Energy performance comparison between the variable refrigerant flow (VRT) and conventional air-conditioning and mechanical ventilation (ACMV) systems for tropical buildings / Muhammad 'Amir Roslan - Muhammad 'Amir, Roslan (2019)
Generally, an enormous amount of energy is consumed by the large buildings due to the usage of low efficiency and poor thermal performance air - conditioning and mechanical ventilation (ACMV) system. The variable refrigerant flow (VRF) system has found its place in a building due to its high efficiency air - conditioning design. However, it is important to study the real performance of this system under actual operating situations before installing this system in new or retrofitted building in order to achieve energy savings goal. This research is focused on the annual energy consumption of VRF system in the tropical area (Malaysia) and compared it with other ACMV systems, which are split type unit and multi - split type unit systems under the same indoor and outdoor conditions. TRNSYS software is used to simulate the energy consumption for both VRF and ACMV systems based on the existing building’s characteristic and operation. Note that the bin method is applied in finding the annual energy consumption for these systems, thus the baseline simulation in the research is created based on the bin method concept. This research is divided into two case studies according to the types of the building. In case study I, the VRF system is compared with the split type unit in a small building which needs cooling in single zone while for case study II, the VRF system is compared with the multi - split type unit in a large building which needs cooling in several zones. The reason for choosing these types of building is to identify whether the VRF system is suitable to use either in the building with several zones of cooling or building with single zone of cooling or both. For both case studies, simulation results have indicated that the VRF system saves about 15.57% and 13.62% when compared with the split type unit system and multi - split unit system, respectively. The operating cost for these systems is also pointed out and the results indicated that the annual operating cost for the VRF system is 15.64% and 13.63% lower than the split type unit system and multi - split unit system, respectively. This shows that the VRF system has a high potential for energy savings and could reduce significant electricity consumption in the building located in the tropic. Besides, the percentage uncertainty between the both simulation and manually calculation results on the annual energy consumption for these systems are too small which is approximately to 1%, where it shows that the bin method is appropriate to use in the simulation program for energy analysis.